العوامل الاجتماعية والاقتصادية المؤثرة على آراء وتصور الطالبات حول الخصوبة ومحددتها دراسة ميدانية على عينة من طالبات جامعة الوادي - وصيف فائزة, خير الدين; مسعي أحمد, حمزة; لبزة, هشام (جامعة الوادي - University of Eloued, 2021)
حاولنا من خلال هذه الدراسة معرفة آراء وتصورات الطالبات حول واقع الخصوبة وحول أهم المحددات الاجتماعية والاقتصادية المؤثرة عليها، باختيار عينة متكونة من 150 طالبة بجامعة الوادي مختارة بطريقة طبقية. وتوصلنا إلى أن الدخل الشهري المنخفض، عمل المرأة وصحتها إضافة إلى ممارسة النشاط الصناعي من طرف العائلة أهم الأسباب التي تدفع إلى تقليص عدد الأطفال. كما أكد أغلبية الطالبات على أن عدد المواليد سيرتفع وسن الزواج سينخفض بتحسن الظروف المعيشية للأفراد. Through this study, we tried to identify the opinions and perceptions of female students about the reality of fertility and the most important social and economic determinants affecting them, by selecting a sample of 150 students at El-Oued University selected in a class way. We have concluded that low monthly income, women's work and health, as well as the practice of industrial activity by the family, are the main reasons for reducing the number of children. The majority of female students also confirmed that the number of births would increase and the age of marriage would decline as the living conditions of individuals improved.
The socio-economic factors that affect the female students' opinions and perceptions about fertility, which were determined by a field study on a sample of the El-Oued University students
مقال
Keywords: الخصوبة، المحددات الاجتماعية، عدد الأطفال